2002
DOI: 10.1002/mds.10299
|View full text |Cite
|
Sign up to set email alerts
|

Leg muscle strength is reduced in Parkinson's disease and relates to the ability to rise from a chair

Abstract: Individuals with Parkinson's disease (PD) have difficulties rising from a chair; however, factors contributing to this inability have never been investigated. This study compared lower extremity strength between individuals with PD and healthy controls and quantified the relationships between strength and the ability to rise from a chair. Ten males with mild PD and ten male agematched controls performed maximal concentric, isokinetic knee and hip extensor torque on an isokinetic dynamometer to quantify muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
142
1
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(165 citation statements)
references
References 31 publications
14
142
1
8
Order By: Relevance
“…However, they did not assess the lower limb muscles. Another study, which analyzed peak torque measures of the trunk and lower limbs, also reported poorer performance of the proximal muscles in relation to the distal ones in individuals mildly affected by PD 23 . In the present study, knee extensors at 30°/s and ankle dorsiflexors at both speeds demonstrated no significant differences in performance, compared to the control group.…”
Section: Discussionmentioning
confidence: 94%
“…However, they did not assess the lower limb muscles. Another study, which analyzed peak torque measures of the trunk and lower limbs, also reported poorer performance of the proximal muscles in relation to the distal ones in individuals mildly affected by PD 23 . In the present study, knee extensors at 30°/s and ankle dorsiflexors at both speeds demonstrated no significant differences in performance, compared to the control group.…”
Section: Discussionmentioning
confidence: 94%
“…Alexander et al (1997) reported that frail older adults who used a hip strategy had reduced knee and hip extensor moments while Doorenbosch et al (1994) found that this strategy reduced the knee extensor moment, but increased the hip extensor moment in young adults. We recently reported that individuals with mild PD have substantial hip and knee extensor muscle weakness compared to agematched controls (Inkster et al 2003) while others have reported a reduced rate of muscle force generation in PD (Corcos et al 1996;Stelmach and Worringham 1998). A reduced ability to generate force in PD could originate from both peripheral and central mechanisms.…”
Section: Altered Movement Strategymentioning
confidence: 94%
“…Kirker et al (Kirker et al, 2000) suggest that the unloading of the swing limb is accompanied by increased activity of the stance leg gluteus medius and swing leg adductors. The reduction in the ability to shift weight in the mediolateral direction during gait initiation for patients with PD may be a result of the known alterations in proximal musculature strength (Lawrence and Kuypers, 1968) and the muscles surrounding the hip in particular (Inkster et al, 2003).…”
Section: Lateral-oriented Gait Initiationmentioning
confidence: 99%
“…Further, control parameters such as the relationship between the COP and COM may have provided greater information regarding differences in dynamic balance control in these two populations. The magnitude of the separation between the COP and COM, referred to as the COP-COM moment arm, relates to the subject's tolerance of dynamic unsteadiness, generation of forward momentum, and is a valid tool for discriminating unsteady older adults from healthy older adults or those with balance dysfunction (Inkster et al, 2003). Last, electromyographic recordings would have been beneficial in helping to explain differences in the COP displacements between the populations of interests.…”
Section: Lateral-oriented Gait Initiationmentioning
confidence: 99%